2019
DOI: 10.1088/1361-6501/ab03ba
|View full text |Cite
|
Sign up to set email alerts
|

An improved matching pursuit method for overlapping echo separation in ultrasonic thickness measurement

Abstract: Overlapping of reflected ultrasonic echoes is a universal physical phenomenon, when the measured thickness is less than a limit threshold (e.g. 1mm for metallic materials using conventional processing methods). Generally, two typical signal states may be generated in this situation: highly overlapping and distorted overlapping. If the overlapping echoes cannot not be separated precisely, significant measurement errors will inevitably occur. In this research, an improved matching pursuit method for overlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…To realize the ultrasonic thickness scanning process, a multi-functional and highly integrated ultrasonic on-machine thickness measuring device is designed and the scanning process of the thickness is proceeded on the CNC equipment (Lian et al, 2019a; Lian et al, 2019b), as shown in Figure 1. It is composed of a programmable multi-axis controller, eight servo drivers, eight servo motors, a force sensor, an ultrasonic probe, a data acquisition card, and an industrial computer.…”
Section: Ultrasonic Scanning Processmentioning
confidence: 99%
“…To realize the ultrasonic thickness scanning process, a multi-functional and highly integrated ultrasonic on-machine thickness measuring device is designed and the scanning process of the thickness is proceeded on the CNC equipment (Lian et al, 2019a; Lian et al, 2019b), as shown in Figure 1. It is composed of a programmable multi-axis controller, eight servo drivers, eight servo motors, a force sensor, an ultrasonic probe, a data acquisition card, and an industrial computer.…”
Section: Ultrasonic Scanning Processmentioning
confidence: 99%
“…Matching pursuit (MP) [73], [82], [94] methods of signal decomposition, on the other hand, offer a flexible approach for representing signals in terms of localized structures using a selected basis. MP does not suffer from inherent resolution limitations and does not assume a static echo shape along the depth of the signal.…”
Section: Matching Pursuitmentioning
confidence: 99%
“…Separation of overlapping echoes is a problem that is studied in ultrasound nondestructive evaluation and biomedical applications. MP methods of decomposition have received attention in ultrasound nondestructive evaluation [82], [102], [103], and demonstrated success despite drawbacks in the MP algorithm such as the greedy selection resulting in suboptimal echo estimates and the tendency to converge to global signal structures. IMT estimation requires the depth location of the echoes from the lumen-intima and media-adventitia boundaries of the artery wall.…”
Section: Intima-media Thickness Estimationmentioning
confidence: 99%
See 2 more Smart Citations